THE IMPACT OF CULTURAL A ND HISTORICAL CONTEXTS ON THE POLYSEMY OF MILITARY TERMINOLOGY IN ENGLISH, UZBEK, AND RUSSIAN LANGUAGES - Dilnoza Aminova (American Journals Publishing, 2023)
The use of military terminology in different languages is influenced by cultural and historical contexts. This study aims to examine the impact of cultural and historical contexts on the polysemy of military terminology in English, Uzbek, and Russian languages. The research focuses on analyzing the meanings and usages of military terminology in these languages and how they differ from one another. By doing so, the study will provide a better understanding of the role that cultural and historical contexts play in shaping the meanings of military terminology.
Keywords: Military terminology, polysemy, cultural context, historical context